2020
DOI: 10.1186/s13148-020-00832-6
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 is associated with TFF2 methylation in gastric cancer

Abstract: Background: Emerging evidence has shown that MUC1 and TFF2 play crucial roles in the H. pylori-infected pathogenesis of gastric cancer (GC). A recent study revealed that H. pylori infection induced obviously increased Tff2 methylation levels in Muc1 −/− mice compared with controls. However, little is known of the molecular mechanism on MUC1 regulating the expression of TFF2. Methods: We conducted a correlation analysis of MUC1 and TFF2 in public databases and our adjacent GC tissues. Besides, MUC1 overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…46 Moreover, MUC1 was associated with methylation of TFF2, a member of secreted peptides, which is also expressed in gastric mucosa and triggers cell migration signaling to promote epithelial repair and involve in GC development. 47 Therefore, MUC1 played a key role in the development of many human cancers including HCC.…”
Section: Discussionmentioning
confidence: 99%
“…46 Moreover, MUC1 was associated with methylation of TFF2, a member of secreted peptides, which is also expressed in gastric mucosa and triggers cell migration signaling to promote epithelial repair and involve in GC development. 47 Therefore, MUC1 played a key role in the development of many human cancers including HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of MUC1 suggests that MUC1 can be rendered as an antibody-based therapeutic target 27 and inhibiting MUC1 expression also could suppress cancer cell migration as a novel therapeutic approach to pancreatic cancer treatment. 28 The overexpression of MUC1 was directly associated with the apoptosis pathway 29 and gastric cancer, 30 indicating it could be considered a high-risk factor for the prognosis of gastrointestinal carcinoma. Szlendak et al 31 reported that decreased expression of MUC2 secreted gel-forming mucin is generally observed in colorectal adenocarcinoma, while increased expression of MUC1 was observed in colorectal cancer, indicating low oral doses of BaP could alter MUC expression via colonic injury.…”
Section: Discussionmentioning
confidence: 99%
“…The types and abundance of immune cell infiltration in the tumor microenvironment have proved to be very different from normal tissues [ 14 ]. Studies have found that the expression of MUC1 induces immune suppression in colon cancer, and this suppression can be reversed by blocking the PD1/PDL1 pathway [ 15 ]. MUC1 has shown a strong potential in the diagnosis and treatment of tumors.…”
Section: Introductionmentioning
confidence: 99%